2019
DOI: 10.3126/jcmsn.v15i3.24363
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Profile of Burn Patients and Antimicrobial Susceptibility Pattern of their Wound Isolates at Nepal Cleft and Burn Center

Abstract: Background: Burn infections are the major causes of morbidity and mortality in burn patients. The infectious agent could be both Gram positive and Gram negative bacteria. The aim of this research was to study the bacteriological profile of burn patients and anti-microbial susceptibility pattern of their wound isolates.  Methods: This cross-sectional study was conducted in Kirtipur Hospital, Nepal from January 1st to March 31st 2019. A total of 109 burn patients were included and their wound swabs were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…The antibiotic sensitivity test using the Vitek2 Compact System showed that the resistance rate was recorded in Staphylococcus aureus against Amikacin by 13 isolates, with a rate of 86.6%, and in Acinetobacter baumannii, towards Ceftazidime and Piperacillin antibiotics by 12 isolates at a rate of 100%, and Pseudomonas aeruginosa towards Colistin and Tobramycin at a rate of 6 isolates at a rate of 60%, and Klebsiella pneumoniae towards Colistin and Tobramycin at a rate of 8 isolates at a rate of 100% and Escherichia coli against Amikacin, Colistin and Imipenem with 7 isolates and 100%, and Proteus mirabilis against Colistin and Tobramycin with 6 isolates and 100%, and Burkholderia cepacia against 8 antibiotics with a rate of 100%. These results are in agreement with many studies [27,28]. Burn wound infection remains a serious problem for burn patients as many bacteria develop varying degrees of resistance to most known antibiotics.…”
Section: Discussionsupporting
confidence: 93%
“…The antibiotic sensitivity test using the Vitek2 Compact System showed that the resistance rate was recorded in Staphylococcus aureus against Amikacin by 13 isolates, with a rate of 86.6%, and in Acinetobacter baumannii, towards Ceftazidime and Piperacillin antibiotics by 12 isolates at a rate of 100%, and Pseudomonas aeruginosa towards Colistin and Tobramycin at a rate of 6 isolates at a rate of 60%, and Klebsiella pneumoniae towards Colistin and Tobramycin at a rate of 8 isolates at a rate of 100% and Escherichia coli against Amikacin, Colistin and Imipenem with 7 isolates and 100%, and Proteus mirabilis against Colistin and Tobramycin with 6 isolates and 100%, and Burkholderia cepacia against 8 antibiotics with a rate of 100%. These results are in agreement with many studies [27,28]. Burn wound infection remains a serious problem for burn patients as many bacteria develop varying degrees of resistance to most known antibiotics.…”
Section: Discussionsupporting
confidence: 93%